TESTING THE INTEGRITY OF SCALABLE AND DISTRIBUTED SOFTWARE-AS-A-SERVICE CLOUDS FOR DISTRIBUTED SERVICES. (International Journal of Food and Nutritional Sciences, 2022)
Cloud platforms that provide software-as-a-service (SaaS) have enabled application service providers to host their programs on vast computer networks housed in the cloud. Because SaaS clouds are shared by many people, attacks can occur. The purpose of this essay is to examine the Int Test. The method employed can be expanded and works well to demonstrate the dependability of Software as a Service (SaaS) cloud services. Unlike prior methodologies, Int Test's entire attestation graph analysis method makes it easier to discover the bad actors. Furthermore, utilizing Int Test may increase the precision and dependability of results by replacing bad results produced by malicious attackers with good results produced by reliable service providers. The IBM System S stream processing tools were used to construct and test a modified version of the Int ify system in a real-world cloud computing environment. Our study's findings indicate that employing Int Test may be a more accurate way to locate the culprit than the methods currently in use. The Int Test is regarded to be appropriate for usage in large cloud systems because it requires no additional hardware or secure kernel support and has no effect on software speed